Evidências da produção de redes extracelulares por linfócitos T humanos - Carolina Cattoni Koh (2015)
The release of extracellular traps (ETs) was first described in 2004, in neutrophils, and, thus, the structures were called neutrophil extracellular traps (NETs). The extracellular traps are composed of a DNA skeleton (nuclear or mitochondrial) decorated with antimicrobicidal peptides, proteases and histones. Other cell types, such as mast cells, eosinophils and macrophages, are able to release these structures. The release of ETs is called etosis. Etosis can be characterized as a new type of cell death, different from apoptosis and necrosis. However, in some cases of the trap release, cell death does not occur. It has been shown that ETs have antimicrobial activity against some agents such as bacteria, fungi, viruses and protozoa. It is known that promastigotes and amastigotes of Leishmania are capable of inducing the release of NETs. In addition, histones are able to kill Leishmania promastigotes. Human infection with parasites of the genus Leishmania leads to leishmaniasis, a disease that affects millions of people worldwide. Cutaneous leishmaniasis (CL), the most common form in Brazil, is mainly caused by Leishmania braziliensis and is the mildest form of the disease characterized by the presence of one or few skin ulcers or nodular lesions near the site of the bite of the sand fly, which usually resolves after specific therapy. Mucosal leishmaniasis (ML), also caused by Leishmania braziliensis, is characterized by lesions in the mucosal tissue with no concomitant cutaneous involvement. This clinical form is progressive and destructive in the absence of treatment. T lymphocytes are important and frequent cells in the lesions of patients with CL and ML, are part of the adaptive immune response, and may participate in the elimination of parasites in the lesions by mechanisms not fully understood, that may involve cytotoxicity. Interestingly, this same mechanism appears to be important for the development of lesions. This study aims to characterize the release of ETs by T lymphocytes, using different techniques such as scanning electron microscopy, immunofluorescence and quantification of extracellular DNA. Our results suggest that CD4+ and CD8+ T cells can release ETs. These ETs are present in the lesions of patients with CL and ML, suggesting that they can contribute to the elimination of Leishmania, but also participate in the inflammatory reactivity that leads to the tissue injury. In addition to providing possible new mechanisms associated with the pathogenesis of leishmaniasis, this work provides the first evidence that T lymphocytes are able to release extracellular traps, which may have implications for several biological activities of these cells.